The practical guide to externalising local authority services - Sparke, Andrew (England, 1994)
A practical guide to the legal, personnel, financial and management problems arising in the course of the transfer of local authority services and staff to arms-length and external organizations. Topics covered include: conflicts of interests and elements of transition.